Nitrous oxide emission estimation from managed soils in Argentina: Differences between IPCC 2006 guidelines and the IPCC 2019 refinemet - Said, Andrés Demián; Beltran, Marcelo Javier; Vázquez Amabile, Gabriel (Facultad de Agronomía, Universidad de Buenos Aires, 2023)
Based on the IPCC 2006 guidelines, the total GHG emission for 2016, in Argentina, were estimated to reach a total net 364 MtCO2eq. Particularly, N2O emissions from managed soils sector represented 12% of total emissions. The IPCC 2019 refinement to the 2006 guidelines for GHG inventories provides an up-to-date and robust scientific basis to support the preparation and continuous improvement of estimates. The aims of the present work were to carry out a desk study to estimate nitrous oxide emissions from managed soils, using the IPCC 2019 and to compare this methodology with the one currently used for national GHG inventories (IPCC 2006) in Argentina. The nitrogen sources accounted for GHG emissions were: (i) synthetic fertilizer, (ii) crop residues, (iii) mineralization from soil organic matter, (iv) urine and dung from grazing animals, and (v) organic fertilizer. The adoption of the updated emission factors from the 2019 IPCC refinement would have a significant impact on the estimation of nitrous oxide (N2O) emissions. Compared to the 2006 IPCC guidelines, the application of these factors in Argentina would lead to decrease emissions from managed soils in 18.95 MtCO2eq, representing a 46% reduction for this category. This reduction would be significant in the greenhouse gases (GHG) inventories of Argentina (by approximately 5%), and for other countries with similar economies. These changes might affect the prioritization of mitigation actions for the analyzed categories, when considering cost and benefits.